Perpetual anarchy: From economic security to financial insecurity - Sonja M. Amadae (Finance and Society, 2017)
This forum contribution addresses two major themes in de Goede's original essay on "Financial security": (1) the relationship between stable markets and the proverbial "security dilemma"; and (2) the development of new decision-technologies to address risk in the post-World War II period. Its argument is that the confluence of these two themes through rational choice theory represents a fundamental re-evaluation of the security dilemma and its relationship to the rule of law governing market relations, ushering in an era of perpetual physical and financial insecurity.
Keywords: 300